Stick, Carrot and Skill Acquisition - Trine Filges; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2001)
This paper examins the macroeconomic effects of youth unemployement programmes in the form of vocational training (YUPs), developing a two sector general equilibrium model featuring matching frictions and worker-firm wage bargaining for skilled workers. Unskilled sector wages are indexed to skilled sector wages. Workers differ with respect to ability, having importance for the young worker`s skill decision. Furthermore, a young worker may be offered vocational training through YUPs. The total number of skilled workers is therefore determined by these two channels and the interaction between them. We focus on the impact of YUPs on skill division, unemployment distribution workers and aggregate unemployment.
hdl:10398/7601
Keywords: J18; J38; J68; 330; Skill acquisition; Search; Unemployment